(untitled) - Jantzen, Jan (Chichester, England, 2007)
This book is an invaluable resource for a broad spectrum of researchers, practitioners, and students in engineering. In particular it is especially relevant for those in mechanical and electrical engineering, as well as those in artificial intelligence, machine learning, bio-informatics, and operational research. It is also a useful reference for practising engineers, working on the development of fuzzy control applications and system architectures
Keywords: Automatic control,Fuzzy systems,Fuzzy automata,Điều khiển tự động,Nguyên lý tự động mờ